Experimental Paracoccidioides brasiliensis infection in mice : influence of the hormonal status of the host on tissue responses (2002)
ABSTRACT: We have previously proposed that 17b -estradiol may be responsible in part for the decreased frequency of clinical paracoccidioidomycosis in females via a blocking of the initial morphological transformation necessary to initiate infection. Here we examined the course of infection in male and female mice in relation to their hormonal status. After pulmonary infection with conidia, normal males showed progressive infection, whereas normal females restricted proliferation and progressive disease. In contrast, castrated animals exhibited lesser capacity to restrict disease progression. Castrated male mice reconstituted with 17b -estradiol initially restricted proliferation, but showed disease progression later in infection, whereas castrated female mice reconstituted with testosterone were unable to restrict disease. Quantitative histological analyses demonstrated that only normal male and castrated reconstituted mice developed granulomas, which decreased in number and size with time correlating with increasing numbers of CFU in the lungs. Greater numbers of chronic in ammatory foci did not correlate with higher CFU. These results further support a role for 17b -estradiol during early innate resistance of females to paracoccidioidomycosis.